PENGGUNAAN QUALITY FUNCTION DEPLOYMENT (QFD) SEBAGAI DASAR PENILAIAN KINERJA LAYANAN PUSKESMAS DI KOTA PROBOLINGGO - Noor Farid (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2017)
This study aims to describe how the concept of Quality Function Deployment (QFD) can be used as the basis of performance appraisal services at puskesmas in Probolinggo. The specialty of the QF) method is that the primary focus is the requirements of the customer. Processes are driven by what the customers want, not by innovation in technology. Consequently, more effort must be made in obtaining the information necessary to determine what customers really want. This research uses qualitative approach with case study design. The location of this research is at Puskesmas Probolinggo. Data sources were obtained from patients undergoing treatment at Puskesmas Probolinggo. Variable in this research is characteristic of desire and expectation of customer or society to service quality, characteristics of service quality aspect and organizational characteristic based on customer perception. The result of the research shows that order to improve the quality of service at puskesmas especially in Probolinggo city needs a method of measuring and identification of the quality of service and one of method of measuring quality of service is QFD.